SME GOVERNANCE AND STAFFS EMPOWERMENT ON SMEs PERFORMANCE IN SEMARANG - Moh Ali Shahab (Jurnal Ilmiah Ekonomi Bisnis, 2012)
This study aims to determine the effect of employee empowerment and good corporategovernance to company performance, particularly on small and medium enterprises(SMEs). SMEs for these long are more important in promoting economic growth, thereforeincreasing the performance of SMEs needed to get the most attention in this study.Study sample was 101 managers or small business owner with a purposive samplingtechnique sampling. Data collection method is done by using a questionnaire. Based onthe results of research using moderating regression analysis (RMA), employeeempowerment has a significant effect on the performance of the company. Corporategovernance has a significant effect on the performance of the company. Interaction ofemployee empowerment and corporate governance does not affect the performance of thecompany, in the sense that corporate governance is not able to moderate the relationshipempowering employees with the company’s performance.Key Words: Empowerment of employees, Corporate Governance, Performance, SMEs